A computational framework for electrification of liquid flows. (January 2022) - Calero, Mathieu; Grosshans, Holger; Papalexandris, Miltiadis V.
Abstract: Flow electrification constitutes a significant hazard to operational safety in industry and for this reason it has been studied in detail over the years. It is generally accepted that the impact of turbulence on the electrification of liquids is of paramount importance. More specifically, at sufficiently high Reynolds numbers and for low-conductivity liquids such as hydrocarbons, the thickness of the hydrodynamic boundary layer can become comparable to that of the electrical double layer. This can lead to increased charge diffusion towards the bulk of the flow and, subsequently, flow electrification. However, quantitative information of the underpinning mechanisms of this phenomenon is still lacking. In this paper we present a computational framework for the study of electrification of liquid flows via numerical simulations. In the first part of the paper, we present the governing equations and describe the proposed algorithm and its implementation in pafiX, which is a computational tool for the simulation of fluid flows related to explosion protection. In the second part, we present results from numerical tests that we performed in order to access the efficiency of the proposed computational framework. Highlights: A new computational method is proposed to compute transport of electric charges in flows of liquid dielectrics as benzene and other liquid hydrocarbons. The proposed algorithm solves simultaneously the coupled equations of the fluid flow and the electric field. The efficiency of the proposed algorithm is tested against a series of validation tests.